2014
DOI: 10.1002/mds.25927
|View full text |Cite
|
Sign up to set email alerts
|

Multiple system atrophy: Prognostic indicators of survival

Abstract: Background Neurologic and autonomic presentation in multiple system atrophy (MSA) may predict early mortality. Quantification of early autonomic failure as mortality predictor is lacking. Methods Early neurologic and autonomic clinical features were retrospectively reviewed in 49 MSA cases (median age at onset, 56.1 years; 16 women) confirmed by autopsy at Mayo Clinic. When available, the 10-point composite autonomic severity score derived from the autonomic reflex screen provided quantification of the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
64
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 33 publications
15
64
3
Order By: Relevance
“…Our study showed poor survival prognosis for patients with higher ages at disease onset, and this result was consistent with that of previous studies [15,16]. Our study…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed poor survival prognosis for patients with higher ages at disease onset, and this result was consistent with that of previous studies [15,16]. Our study…”
Section: Discussionsupporting
confidence: 93%
“…Thereby we demonstrate that PET is a prognostic marker on its own. However, the good agreement between the disease-specific survival data of the present PET study and earlier postmortem studies also provides indirect support to the notion that metabolic patterns are valuable means for differential diagnosis (2)(3)(4)(5)7,13).…”
Section: Discussionsupporting
confidence: 79%
“…APSs are characterized by a rapid progression to disability and death. According to clinical and clinicopathologic studies, MSA, PSP, and CBD share a comparably short survival time of about 7-8 y from symptom onset or less than 3-4 y from clinical diagnosis (1)(2)(3)(4)(5)(6)(7)(8). Survival in PD is distinctly better: although some population-based studies did not find higher mortality (9), others convincingly demonstrated an increased age-adjusted mortality in PD (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms include an array of additional clinical features, including pyramidal, respiratory, and behavioral symptoms [2] . MSA patients have a poor prognosis, with a reported survival of 6-9 years from disease onset [3][4][5] .…”
mentioning
confidence: 99%